2018
DOI: 10.1007/s13361-018-1910-5
|View full text |Cite|
|
Sign up to set email alerts
|

Distinct Stabilities of the Structurally Homologous Heptameric Co-Chaperonins GroES and gp31

Abstract: The GroES heptamer is the molecular co-chaperonin that partners with the tetradecamer chaperonin GroEL, which assists in the folding of various nonnative polypeptide chains in Escherichia coli. Gp31 is a structural and functional analogue of GroES encoded by the bacteriophage T4, becoming highly expressed in T4-infected E. coli, taking over the role of GroES, favoring the folding of bacteriophage proteins. Despite being slightly larger, gp31 is quite homologous to GroES in terms of its tertiary and quaternary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 54 publications
(52 reference statements)
4
11
0
Order By: Relevance
“…48 In fact, R47 and K55 residues form salt bridges with neighboring residues in only two subunits and these stabilizing interactions are missing in the other five subunits. This structural heterogeneity 35 might also explain the observation of monomer and dimer ions in native mass spectrum of GroES7 (Figure 3) and previous studies. 32,35 The energy requirement for disassembly of the GroES complex can be compensated by the binding energy to GroEL14.…”
Section: T-dependent Groel-groes Interactionssupporting
confidence: 79%
See 2 more Smart Citations
“…48 In fact, R47 and K55 residues form salt bridges with neighboring residues in only two subunits and these stabilizing interactions are missing in the other five subunits. This structural heterogeneity 35 might also explain the observation of monomer and dimer ions in native mass spectrum of GroES7 (Figure 3) and previous studies. 32,35 The energy requirement for disassembly of the GroES complex can be compensated by the binding energy to GroEL14.…”
Section: T-dependent Groel-groes Interactionssupporting
confidence: 79%
“…This structural heterogeneity 35 might also explain the observation of monomer and dimer ions in native mass spectrum of GroES7 (Figure 3) and previous studies. 32,35 The energy requirement for disassembly of the GroES complex can be compensated by the binding energy to GroEL14. Previous studies have shown that both ATP and GroES binding are necessary for apical domain movement and for transition from substrate-binding mode (hydrophobic surface exposed) to the folding-active state (hydrophilic chamber).…”
Section: T-dependent Groel-groes Interactionssupporting
confidence: 79%
See 1 more Smart Citation
“…26,34 The midpoint in the melting curve (Figure 2E) is used to estimate the melting point (Tm) of ~ 48.5 °C, (see experimental section) which is significantly lower than the Tm of ~74 °C reported by Boudker et al 35 It is important to note, however, that their DCp vs. T curve revealed evidence for a low temperature endotherm at ~40 o C, which agrees well with our Tm for GroES7. Geels et al 36 and Dyachenko et al 37 have reported Tm data for GroES using mass spectrometry, and they report similar Tm values (~70 o C), but both of these studies were performed using ammonium acetate buffer. Moreover, the DSC and vT-ESI results reveal strong evidence for T-dependent instability, and the vT-ESI results suggest that this transition may serve as the early steps leading to disassembly of GroES7 complex.…”
Section: Thermal Stability Of Groel and Groes As Determined By Vt-esi Native Msmentioning
confidence: 96%
“…This structural heterogeneity 37 might also explain the observation of monomer and dimer ions in native mass spectrum of GroES7 (Figure 3) and previous studies. 33,37 The energy requirement for disassembly of the GroES complex can be compensated by the binding energy to GroEL14. Previous studies have shown that both ATP and GroES binding are necessary for apical domain movement and for transition from substrate-binding mode (hydrophobic surface exposed) to the folding-active state (hydrophilic chamber).…”
Section: T-dependent Groel-groes Interactionsmentioning
confidence: 99%